LIGHT RAIL TRANSIT PUBLIC TRANSPORTATION QUEUE SYSTEM BASED ON ANDROID - Fransisco, Roy; Arifitama, Budi (Jurnal Algoritma, Logika dan Komputasi, 2020)
The more advanced and the development of the era tends to create more complex problems that needs to be solved. Queueing in Indonesia is a problem that is difficult to control. LRT (Light Rail Transit) is the most recent public transportation for the people living around Northern Jakarta. Most of the people want to try this new transportation, This creates a problem where usually people tend to not queueing in line when buying tickets. The solution fot this problem is by ordering online tickets or online queues over queueing traditionally. In this study, the Designing and programming methods used C # code on visual studio which is performed as a form of validation such as validation for Login and Registering; PHP code is used to connect the database for data registrants, users, and admin; and UML (Unified Modeling Language) for designing the system and database. With this online queue, it can help overcome the problem of crowded long and congested lines at the LRT station so that it can increase the culture of the queue for mutual order to be realized.